2011
DOI: 10.3961/jpmph.2011.44.5.191
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Effects on Post-Traumatic Stress Disorder (PTSD) in Female North Korean Immigrants

Abstract: ObjectivesThe goal of this paper is to examine the social network effects on post-traumatic sdress disorder (PTSD) in female North Korean immigrants who entered South Korea in 2007. Specifically, it attempts to verify if the density and composition of networks make a difference after controlling for the network size.MethodsA multivariate logistic regression is used to probe the effects of social networks using the North Korean Immigrant Panel data set. Because the data set had only completed its initial survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
(15 reference statements)
1
12
0
Order By: Relevance
“…With regard to marital status, most of the PTSD sufferers in our sample were married, and therefore this pattern of results reflects previous findings [29,30,31]. Turning to educational level, most of the PTSD sufferers were below diploma level, suggesting that PTSD may be more common in people with little education.…”
Section: Discussionsupporting
confidence: 74%
“…With regard to marital status, most of the PTSD sufferers in our sample were married, and therefore this pattern of results reflects previous findings [29,30,31]. Turning to educational level, most of the PTSD sufferers were below diploma level, suggesting that PTSD may be more common in people with little education.…”
Section: Discussionsupporting
confidence: 74%
“…In contrary, the study conducted in Portugal showed network in large sample compared their contacts, subjects do not connect very much (density=2.5%) [33] and the one in Kentucky where network density of infection prevention staffs in hospitals is 1.8% which seems the actors might use to protect themselves by limiting their contacts in this case [34]. But in other study individual's network density is 69% that shows good interconnections, so the difference might be due to the difference in setting, and the purpose [35] which still increases something to look in our study.…”
Section: Study Definitionsmentioning
confidence: 99%
“…Dekker and Krackhardt discussed as it could show the association between data on interpersonal relations [40] and individuals with similar characteristics others, who in turn get many responses, the actor is at the centre of teams [30]. In other way degree of centrality is the proportion of actors that send or receive responses to or from that actor [35].…”
Section: Study Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Having social support is known to protect people from postdisaster psychological distress 17,18 and alleviate the conditions related to traumatic loss due to disasters. [19][20][21] However, research also indicates that perceived social support, and the quantity and quality of interpersonal relationships, may decrease after disasters. 12,22 The decline in perceived social support could partly explain physical and mental health problems among the survivors.…”
mentioning
confidence: 99%